Genomic prediction of yield-related traits and genome-based establishment of heterotic pattern in maize hybrid breeding of Southwest China - Xiang, Yong; Xia, Chao; Li, Lujiang; Wei, Rujun; Rong, Tingzhao; Liu, Hailan; Lan, Hai (Frontiers in Plant Science, 2024)
When genomic prediction is implemented in breeding Maize (Zea mays L.), it can accelerate the breeding process and reduce cost to a large extent. In this study, 11 yieldrelated traits of maize were used to evaluate four genomic prediction methods including rrBLUP, HEBLP|A, RF, and LightGBM. In all the 11 traits, rrBLUP had similar predictive accuracy to HEBLP|A, and so did RF to LightGBM, but rrBLUP and HEBLP|A outperformed RF and LightGBM in 8 traits. Furthermore, genomic prediction-based heterotic pattern of yield was established based on 64620 crosses of maize in Southwest China, and the result showed that one of the parent lines of the top 5% crosses came from temp-tropic or tropic germplasm, which is highly consistent with the actual situation in breeding, and that heterotic pattern (Reid+ × Suwan+) will be a major heterotic pattern of Southwest China in the future.